Influence of Non-Thermal Plasma Treatment on Structural Network Attributes of Wheat Flour and Respective Dough - Khan, Muhammad Jehanzaib; Jovicic, Vojislav; Zbogar-Rasic, Ana; Zettel, Viktoria; Delgado, Antonio; Hitzmann, Bernd (Foods, 2023)
Due to its “generally recognized as safe status” (GRAS) and moderate treatment temperatures, non-thermal plasma (NTP) has lately been considered a suitable replacement for chemicals in the modification of food properties and for preserving food quality. One of the promising areas for the application of NTP is the treatment of wheat flour, leading to improved flour properties and product quality and consequently to higher customer satisfaction. In the present research, the German wheat flour type 550, equivalent to all-purpose flour, was treated using NTP in a rotational reactor to determine the influence of short treatment times (≤5 min) on the properties of flour (moisture and fat content, protein, starch, color, microbial activity, and enzymes), dough (visco-elastic properties, starch, wet and dry gluten, and water absorption), and baking products (color, freshness, baked volume, crumb structure, softness, and elasticity). Based on the properties of NTP, it was expected that even very short treatment times would have a significant effect on the flour particles, which could positively affect the quality of the final baking product. Overall, the experimental analysis showed a positive effect of NTP treatment of wheat flour, e.g., decreased water activity value (<0.7), which is known to positively affect flour stability and product shelf life; dough stability increased (>8% after 5 min. treatment); dough extensibility increased (ca. 30% after 3 min treatment); etc. Regarding the baking product, further positive effects were detected, e.g., enhanced product volume (>9%), improved crumb whiteness/decreased crumb yellowness, softening of breadcrumb without a change in elasticity, and limited microorganism and enzymatic activity. Furthermore, no negative effects on the product quality were observed, even though further food quality tests are required. The presented experimental research confirms the overall positive influence of NTP treatment, even for very low treatment times, on wheat flour and its products. The presented findings are significant for the potential implementation of this technique on an industrial level.
CRIS-Team Scopus Importer:2023-06-09
Keywords: cold plasma; dough rheology; hydration; microbial activity; microstructure; protein and starch properties; wheat flour